Prevalence of lower urinary tract symptoms in antenatal women in a tertiary care teaching institute of Uttar Pradesh - Upadhyay, Anupma; Aparna; Kapoor, Abhivyakti; Srivastava, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Lower urinary tract symptoms (LUTS) are common in pregnancy due to hormonal, anatomical, and physiological changes, posing risks for both maternal and fetal health. Early detection is critical to prevent complications such as pyelonephritis, preterm labor, and low birth weight. Aim was to determine the prevalence of lower urinary tract symptoms among antenatal women. Methods: This cross-sectional observational study was conducted at MLN Medical College, Prayagraj, from October 2024 to March 2025. One hundred symptomatic antenatal women were assessed through detailed history, examination, and lifestyle evaluation. Women with pre-existing urological conditions, immunocompromise, or recent urinary instrumentation were excluded. Results: Most participants were aged 25-29 years (42%), multigravida (82%), in the first trimester (67%), from lower middle socioeconomic backgrounds (68%), and urban areas (65%). The predominant symptom was burning sensation/pain during micturition (56%), followed by increased frequency (32%). While 65% consumed ≥2 liters water daily and 80% had >2000 kcal/day intake, LUTS remained prevalent. Lifestyle factors included exercise (49%), tobacco chewing (23%), and caffeine use (13%). Conclusions: LUTS in pregnancy are prevalent even among women with adequate hydration and nutrition, suggesting multifactorial etiology. Routine screening, lifestyle counselling, and early management- especially in multigravida women in early gestation- are essential to reduce morbidity.